Effect of Waste Ceramic Dust on the Strength Characterstics of the Subgrade of the Flexible Pavement - Zehra, Wasifa (My University, 2019)
Stabilization of the soil is required if soil has the drawback in its required engineering properties for theintend of the construction or for the use as subgrade in the flexible pavement or rigid pavement. For the improvement of the engineering properties of the considered soil stabilization can be done by mixing some additives for the better results of the soil strength. For economic and environmental reasons solid waste can be used as the stabilizer for the reinforcement of the soil. The solid waste has different kind as per their source of production, e.g. Agricultural wastes, Industrial wastes, Mineral wastes etc. Some of these wastes are harmful for nature but the can have good effect if we use them as the stabilizer for the increase in the strength of the soil. Many studies had been done on the soil to improve its properties, in this study we are going to observe the change in the properties of the soil by adding an industrial waste named as Ceramic which will be used in the form of dust. Using Ceramic dust as the stabilizer can improve many geotechnical properties of the soil such as Unconfined Compressive strength of the soil and California bearing ratio of the soil these are the properties to determine the strength of the soil. Results from the CBR tests established that addition of these materials in subgrade soil gives efficient strength to subgrade soil. It was observed that the CBR value increases with increase in Ceramic Dust up to a certain percentage. Flexible pavement has been designed with the modification of the soil with Ceramic dust and observed that at the highest value of CBR at the optimum content of the Ceramic dust there is decrease in the pavement thickness, which leads to the decrease in the cost of construction of the pavement.
Keywords: CERAMIC DUST; FLEXIBLE PAVEMENT; SUBGRADE CBR